Temperature-sensitive controlled-release microcapsule, and preparation method and application thereof
Patent Information
- Application Number
- CN202610835259.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-10
- Publication Date
- 2026-09-11
AI Technical Summary
[0004]针对现有的水化热抑制剂存在的温峰拉缓效果不佳、易造成水泥总放热量下降而影响混凝土后期强度发展、适配性弱、延长混凝土早期凝结时间的问题,本发明的目的为提供一种温敏控释微胶囊及其制备方法和应用,所述温敏控释微胶囊能够对硅酸盐水泥中C3S的水化加速期实现靶向精准调控,在实现温峰有效拉缓的同时不影响最终的放热总量;同时,因靶向调控硅酸盐水泥的固有水化规律而具有更强的普适性,受水泥品种、掺合料类型、水胶比等原材料及配合比影响很小,不会对混凝土的早期凝结和后期强度产生不利影响,且便于工业化大规模生产,适用于各类大体积混凝土工况
为解决现有的水化热抑制剂存在的温峰拉缓效果不佳、易造成水泥总放热量下降而影响混凝土后期强度发展、适配性弱、延长混凝土早期凝结时间的问题,本发明提供了一种温敏控释微胶囊及其制备方法和应用。本发明提供的所述温敏控释微胶囊由外向内依次包括刚性外壳、温敏体膨内壳,以及被所述温敏体膨内壳包裹在内的C3S水化靶向调控芯材,具有“刚性外壳+温敏体膨内壳+C3S水化靶向调控芯材”构成的“双层壳核结构”。
Smart Images

Figure SMS_19 
Figure SMS_22 
Figure SMS_28
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building materials technology, specifically relating to a temperature-sensitive controlled-release microcapsule, its preparation method, and its application. Background Technology
[0002] Large-volume concrete structures are prone to developing significant internal and external temperature differences due to the concentrated heat release during cement hydration and the difficulty in dissipating internal heat. This can lead to temperature cracks and severely impact the durability, integrity, and waterproofing performance of the large-volume concrete structure. To address this, current technologies primarily employ low-heat cement, mineral admixtures, cooling water pipes, or hydration heat inhibitors to control the hydration temperature rise. Among these, hydration heat inhibitors have become the mainstream agent for controlling hydration temperature rise due to their ease of operation and direct effect.
[0003] Existing hydration heat inhibitors are mostly retarding materials, such as sodium gluconate and citric acid, which slow down the hydration process by adsorbing cement particles or complexing calcium ions. Although these retarding materials can reduce the peak temperature rise, they still have many technical drawbacks: First, they can only reduce the peak temperature slightly, and the effect of slowing down the temperature peak is poor, with heat still being released in a concentrated manner; second, the retarding effect can easily lead to a decrease in the total heat release of cement, affecting the later strength development of concrete; third, the activation conditions are greatly affected by the type of cement, the type of admixture, the water-cement ratio, and other raw materials and mix proportions, resulting in poor adaptability; fourth, they can easily cause a significant extension of the early setting time of concrete, affecting the construction progress. Summary of the Invention
[0004] To address the problems of existing hydration heat inhibitors, such as poor temperature peak slowing effect, easy reduction of total cement heat release affecting the later strength development of concrete, weak adaptability, and prolongation of early setting time of concrete, the present invention aims to provide a temperature-sensitive controlled-release microcapsule, its preparation method, and its application. The temperature-sensitive controlled-release microcapsule can achieve targeted and precise control of the accelerated hydration period of C3S in silicate cement, effectively slowing down the temperature peak without affecting the final total heat release. At the same time, due to the targeted control of the inherent hydration law of silicate cement, it has stronger universality and is minimally affected by cement type, admixture type, water-cement ratio, and other raw materials and mix proportions. It will not adversely affect the early setting and later strength of concrete, and is easy to mass-produce industrially, applicable to various large-volume concrete conditions.
[0005] To achieve the above objectives, one aspect of the present invention provides a thermosensitive controlled-release microcapsule, which has a double-shell core structure, comprising, from the outside to the inside, a rigid outer shell, a thermosensitive inner shell, and a C3S hydration-targeting regulation core material encapsulated by the thermosensitive inner shell.
[0006] According to the present invention, the content of the C3S hydration-targeting and regulating core material in the thermosensitive controlled-release microcapsule is 60-70 parts by mass, the content of the thermosensitive inner shell is 20-30 parts by mass, and the content of the rigid outer shell is 10-18 parts by mass.
[0007] According to the present invention, the rigid shell is made of a mixture of calcium silicate gel and polyethylene glycol; and / or The inner shell of the temperature-sensitive body is made of polyethylene glycol / silica composite microspheres; and / or The C3S hydration-targeted regulation core material is a modified polycarboxylic acid ether ester.
[0008] According to the present invention, in the rigid shell, the mass ratio of the calcium silicate gel to the polyethylene glycol is 2:1; Preferably, the polyethylene glycol is polyethylene glycol 400.
[0009] According to the present invention, the phase transition temperature of the polyethylene glycol / silica composite microspheres is 40℃-45℃; and / or the phase transition volume is 15%-20%; Preferably, the particle size of the polyethylene glycol / silica composite microspheres is 50μm-80μm.
[0010] According to the present invention, the polyethylene glycol / silica composite microspheres are surface modified with a silane coupling agent; Preferably, the silane coupling agent is γ-aminopropyltriethoxysilane.
[0011] According to the present invention, the modified polycarboxylic acid ether ester is obtained by grafting maleic anhydride onto a polycarboxylic acid water-reducing agent; Preferably, the number-average molecular weight of the modified polycarboxylic acid ether ester is between 8,000 and 12,000.
[0012] According to the present invention, the particle size of the temperature-sensitive controlled-release microcapsules is ≤75μm.
[0013] The second invention provides a method for preparing temperature-sensitive controlled-release microcapsules as described in the first invention, comprising the following steps: After preparing the C3S hydration-targeted regulation core material into a first emulsion, the temperature-sensitive body inner shell is wrapped around the surface of the emulsion droplet to obtain a single-shell capsule. The rigid outer shell is further wrapped around the surface of the single-shell capsule to produce the temperature-sensitive controlled-release microcapsule.
[0014] According to the present invention, the method includes: The modified polycarboxylic acid ether ester, emulsifier, and water are mixed and emulsified to obtain the first emulsion; Mix the polyethylene glycol / silica composite microspheres and the first emulsion, adjust the pH, and stir to coat the polyethylene glycol / silica composite microspheres onto the surface of the emulsion droplets to form the thermosensitive inner shell, thereby obtaining a second emulsion containing the single-shell capsule; The calcium silicate gel and polyethylene glycol are prepared into a sol, which is then dropped into the stirred second emulsion to react, causing the sol to deposit on the surface of the single-shell capsule, thus obtaining a first suspension containing a double-shell capsule. Anhydrous ethanol and the first suspension are mixed to crosslink and solidify the sol on the surface of the double-shell capsule to form the rigid outer shell, resulting in a second suspension containing the temperature-sensitive controlled-release microcapsules.
[0015] According to the present invention, the pH is adjusted to 7.5 to 8.5; and / or The reaction was carried out at a temperature of 30±2℃ for a duration of 2.5 h; and / or The cross-linking and curing process was achieved by stirring at room temperature for 10 minutes.
[0016] According to the present invention, the polyethylene glycol / silica composite microspheres are first modified with a silane coupling agent, and then mixed with the first emulsion; and / or After cross-linking and curing, the rigid shell is further subjected to static aging to make it dense; and / or The second suspension was separated into solid and liquid phases, and the solid phase was collected, dried, and post-processed to obtain the temperature-sensitive controlled-release microcapsules.
[0017] The third invention provides the application of the temperature-sensitive controlled-release microcapsules according to the first invention or the temperature-sensitive controlled-release microcapsules prepared by the method described in the second invention in the control of temperature rise during cement hydration.
[0018] According to the present invention, the dosage of the temperature-sensitive controlled-release microcapsules is 0.8 wt% to 2.0 wt% of the mass of the cementitious materials in the concrete.
[0019] The beneficial effects of this invention are: To address the problems of existing hydration heat inhibitors, such as poor temperature peak retardation, easy reduction of total cement heat release affecting the later strength development of concrete, weak adaptability, and prolonged early setting time of concrete, this invention provides a temperature-sensitive controlled-release microcapsule, its preparation method, and its application. The temperature-sensitive controlled-release microcapsule provided by this invention comprises, from the outside in, a rigid outer shell, a temperature-sensitive expanded inner shell, and a C3S hydration-targeting regulating core material encapsulated by the temperature-sensitive expanded inner shell, possessing a "double-shell core structure" consisting of a rigid outer shell + a temperature-sensitive expanded inner shell + a C3S hydration-targeting regulating core material.
[0020] Compared with the prior art, the present invention has at least the following advantages: (1) The temperature-sensitive controlled-release microcapsules provided by the present invention accurately release modified polycarboxylic acid ether ester during the accelerated hydration period of C3S, thereby achieving targeted regulation of the accelerated hydration period of C3S with high selectivity. By delaying the nucleation and growth rate of CSH gel, the heat is transformed from concentrated release to uniform release. It only reduces the hydration rate of C3S without changing its final hydration degree, and does not interfere with the hydration of C3A, C4AF, and C2S. Under the premise that the total heat release remains basically unchanged, it achieves excellent temperature peak regulation effect. According to the test, the temperature-sensitive controlled-release microcapsules provided by the present invention can reduce the peak hydration temperature rise by about 10°C, broaden the duration of the temperature peak from 12h to more than 30h, and the change rate of total heat release in 7 days (compared to the blank group without the addition of temperature-sensitive controlled-release microcapsules) is <5%. It does not affect the early setting and later strength development of concrete, and can also improve the durability of large-volume concrete in terms of crack resistance, impermeability and frost resistance.
[0021] (2) The thermosensitive controlled-release microcapsules provided by this invention use the inherent accelerated hydration period of C3S in silicate cement (characteristic temperature 40℃ to 45℃, CSH gel nucleation and growth process) as the excitation target. This process is not affected by the type of mineral admixtures, water-cement ratio, sand ratio, or other raw materials and mix proportions, thus making it suitable for various silicate cements and large-volume concrete mix proportions. Tests have shown that the thermosensitive controlled-release microcapsules provided by this invention are effective against "P I 52.5, P S 42.5R, P The three types of silicate cement, F 32.5R, were combined with three different water-cement ratios (0.3 / 0.4 / 0.5) and two different mineral admixtures (30% slag / 40% fly ash) to form a total of 18 concrete formulations. All of these formulations achieved excellent control effects, including a reduction of the peak hydration temperature rise by about 10°C, a temperature peak broadening to more than 30 hours, a 7-day total heat release change rate of less than 5%, and normal early setting and later strength development of concrete. Therefore, the temperature-sensitive controlled-release microcapsules provided by this invention can be directly used for various concrete working conditions without adjusting the formulation for different working conditions.
[0022] (3) In the thermosensitive controlled-release microcapsules provided by the present invention, the thermosensitive expansion shell formed by polyethylene glycol / silica composite microspheres remains stable at room temperature (<40℃) without phase expansion, and the rigid shell made of calcium silicate gel and PEG-400 remains dense and stable at room temperature (<40℃). Therefore, it can ensure that the modified polycarboxylic acid ether ester inside is not released prematurely, so the cement can normally experience the induction period and the early stage of the acceleration period. According to the test, compared with the blank group, after the addition of the thermosensitive controlled-release microcapsules provided by the present invention, the initial setting and final setting time of concrete are delayed by less than 1 hour, thus meeting the on-site construction progress requirements and overcoming the defect of poor workability of traditional retarded hydration inhibitors.
[0023] (4) After testing, the temperature-sensitive controlled-release microcapsules provided by the present invention can still achieve the control effect described in (1) to (3) above after being stored at 40°C for 90 days and under a mixing environment at 38°C. It can be seen that the temperature-sensitive controlled-release microcapsules can adapt well to the high temperature storage and extreme mixing environment in summer.
[0024] (5) The various raw materials used in the preparation process of the temperature-sensitive controlled-release microcapsules provided by the present invention are all conventional raw materials in the building materials industry. Among them, the calcium silicate gel in the rigid shell is itself a cement hydration product. It not only realizes the recycling of cement hydration by-products, but also has good compatibility with cement, aggregates, and conventional admixtures (such as water-reducing agents and air-entraining agents) and has no adverse reactions, so it will not affect the workability of concrete.
[0025] (6) The temperature-sensitive controlled-release microcapsules provided by the present invention are prepared by aqueous emulsification coating method, which does not require complicated special equipment, and the raw materials are readily available and the preparation cost is controllable; in addition, the preparation conditions of the temperature-sensitive controlled-release microcapsules are mild and there is no organic solvent pollution, which is more energy-saving and environmentally friendly; furthermore, each step of the temperature-sensitive controlled-release microcapsules is easy to scale up, and the prepared temperature-sensitive controlled-release microcapsules are in powder form, which is convenient for storage, transportation and measurement, and can meet the needs of industrial applications.
[0026] In summary, the temperature-sensitive controlled-release microcapsules provided by this invention at least solve the problems of existing hydration heat inhibitors, such as poor temperature peak retardation effect, easy reduction of total cement heat release affecting the later strength development of concrete, weak adaptability, and prolongation of early setting time of concrete. They can be widely used in the hydration temperature rise control of various large-volume concretes such as bridge abutments, dams, and raft foundations of high-rise buildings to prevent temperature cracks, and have extremely high industrial application value and broad market prospects. Detailed Implementation
[0027] The present invention will be further described below with reference to the embodiments. However, the embodiments of the present invention are merely illustrative examples and should not be construed as limiting the present invention under any circumstances.
[0028] Hydration heat inhibitors are the mainstream agents for regulating hydration temperature rise in existing technologies. They are often used in large-volume concrete to suppress hydration heat, in order to solve the problem that large-volume concrete is prone to forming huge internal and external temperature differences due to the concentrated heat release of cement hydration and the difficulty in dissipating internal heat, which can cause temperature cracks and lead to a deterioration in the durability, integrity and waterproof performance of the structure.
[0029] Sodium gluconate and citric acid are common retarding hydration heat inhibitors, which mainly slow down the hydration process and reduce the peak temperature rise by adsorbing cement particles or complexing calcium ions. However, these retarding hydration heat inhibitors have the following problems: for example, they have a poor effect on slowing down the temperature peak and cannot eliminate the concentrated release of heat; for example, the retarding effect can easily lead to a decrease in the total heat release of cement, which affects the later strength development of concrete; for example, they have poor compatibility, and the activation conditions are greatly affected by the type of cement, the type of admixture, the water-cement ratio and other raw materials and mix proportions; and for example, they are not conducive to the early setting of concrete, which affects the construction progress.
[0030] In addition to the aforementioned retarding hydration heat inhibitors, some temperature-sensitive hydration heat regulation materials have also been developed, such as temperature-sensitive materials based on organic-inorganic complexes. However, these materials use ambient temperature as the sole excitation target, and the temperature threshold is easily affected by the mixing ratio. Furthermore, some ligands are prone to complexing calcium ions, leading to insufficient hydration. Therefore, they still cannot solve the core problems of reduced total heat release and poor compatibility of cement.
[0031] Studies have found that C3S accounts for 50% to 60% of silicate cement, and its hydration heat release accounts for more than 60% of the total heat release of cement. Furthermore, the accelerated hydration period of C3S (specifically 6 to 16 hours, with a characteristic temperature of 40℃ to 45℃) is the only core process in the formation of the temperature rise peak. This process is an inherent hydration law of silicate cement and is minimally affected by raw materials and mix proportions. If this process can be targeted and controlled, slowing down its hydration rate without changing the final degree of hydration, the effect of broadening and reducing the temperature peak while maintaining a essentially unchanged total heat release can be achieved. However, there is currently no research on hydration temperature rise control materials that precisely target the accelerated hydration period of C3S.
[0032] To address the aforementioned challenges of existing hydration heat suppression technologies, the first aspect of this invention provides a thermosensitive controlled-release microcapsule with a dual-shell core structure, comprising, from the outside in, a rigid outer shell, a thermosensitive inner shell, and a C3S hydration-targeting and regulating core material encapsulated by the thermosensitive inner shell.
[0033] As described above, the thermosensitive controlled-release microcapsule provided by the present invention has a double-shell core structure of "rigid outer shell + thermosensitive inner shell + C3S hydration-targeted regulation core material". Firstly, compared with the traditional single-layer shell, the double-layer shell of "rigid outer shell + thermosensitive inner shell" provides a physical protective barrier, which, combined with the thermosensitive intelligent triggering expansion switch function of the thermosensitive inner shell, constitutes a "dual-control triggering mechanism". This effectively avoids false release and premature release of the core material, preventing premature release of the C3S hydration-targeted regulation core material at room temperature, and also avoids the false triggering problem of traditional thermosensitive materials. Secondly, the dual-layer shell structure of "rigid outer shell + temperature-sensitive inner shell" achieves a precise match between dynamics and structure. Specifically, the volume expansion rate of the temperature-sensitive inner shell is designed to match the density of the rigid outer shell, ensuring good stability of the dual-layer shell at room temperature and allowing the volume expansion of the temperature-sensitive inner shell to break through the rigid outer shell at the target temperature, achieving uniform cracking of the dual-layer shell and providing a C3S hydration-targeted core material release rate that matches the C3S hydration rate. Thirdly, both the rigid outer shell and the temperature-sensitive inner shell structure use conventional raw materials from the building materials industry, exhibiting good compatibility with cementitious matrices and no adverse interfacial effects. Fourthly, the dual-layer shell structure of "rigid outer shell + temperature-sensitive inner shell" strengthens the stable controlled release of the C3S hydration-targeted core material through structural synergy, resulting in a lower probability of mechanical breakage than traditional single-layer shells. This allows the temperature-sensitive controlled-release microcapsules to retain an effective content of the C3S hydration-targeted core material and achieves a smooth release of the C3S hydration-targeted core material, which is beneficial for achieving better temperature peak control effects.
[0034] In summary, the temperature-sensitive controlled-release microcapsules provided by this invention achieve precise temperature-controlled rupture through a dual-layer shell structure of "rigid outer shell + temperature-sensitive inner shell," thereby realizing the temperature-sensitive controlled release of the C3S hydration-targeted core material. This allows for the quantitative and precise release of the C3S hydration-targeted core material at appropriate times, targeting and regulating the accelerated hydration phase of C3S. It only slows down the hydration rate of C3S without changing the final degree of hydration, achieving the effect of broadening and reducing the temperature peak while keeping the total heat release essentially unchanged.
[0035] In one specific embodiment of the present invention, the content of the C3S hydration-targeting and regulating core material in the thermosensitive controlled-release microcapsule is 60-70 parts by weight, the content of the thermosensitive inner shell is 20-30 parts by weight, and the content of the rigid outer shell is 10-18 parts by weight; preferably, the content of the C3S hydration-targeting and regulating core material in the thermosensitive controlled-release microcapsule is 60-70 parts by weight, the content of the thermosensitive inner shell is 20-25 parts by weight, and the content of the rigid outer shell is 10-15 parts by weight.
[0036] In this invention, the mass relationship between the C3S hydration-targeting core material, the thermosensitive inner shell, and the rigid outer shell in the thermosensitive controlled-release capsule is limited to the above-mentioned range. The purpose is to maximize the advantages of the double-shell core structure of "rigid outer shell + thermosensitive inner shell + C3S hydration-targeting core material" and release the C3S hydration-targeting core material quantitatively and accurately at the appropriate time.
[0037] In this invention, the material of the rigid outer shell of the thermosensitive controlled-release microcapsule affects its density, while the material of the thermosensitive inner shell affects its phase change expansion trigger temperature and volume expansion rate. The density of the rigid outer shell needs to match the trigger temperature and volume expansion rate of the thermosensitive inner shell to achieve timed, quantitative, and precise release of the C3S hydration-targeted regulation core material. The type of C3S hydration-targeted regulation core material affects its regulation effect on the accelerated hydration phase of C3S. Therefore, the following implementation method is provided.
[0038] In one specific embodiment of the present invention, the C3S hydration-targeted regulation core material is a modified polycarboxylic acid ether ester.
[0039] In a preferred embodiment of the present invention, the modified polycarboxylic acid ether ester has a number average molecular weight of 8,000 to 12,000 and is obtained by grafting maleic anhydride onto a polycarboxylic acid water-reducing agent. The modified polycarboxylic acid ether ester has a significant inhibitory effect on the hydration of C3S, with a C3S hydration inhibition rate of not less than 40%, and has a relatively small impact on the hydration process of other mineral phases in cement, thus enabling targeted regulation (or selective regulation) of C3S hydration.
[0040] The modified polycarboxylic acid ether ester used in this invention is from Tianjin Rumi Jiyue New Materials Co., Ltd.
[0041] In one specific embodiment of the present invention, the inner shell of the temperature-sensitive body is made of polyethylene glycol / silica composite microspheres.
[0042] In one specific embodiment of the present invention, the phase transition temperature of the polyethylene glycol / silica composite microspheres is 40°C to 45°C, the phase transition expansion rate (i.e., the volume expansion rate during phase transition) is 15% to 20%, and the particle size is 50μm to 80μm. The particle size of 50μm to 80μm is beneficial for the aggregation of the polyethylene glycol / silica composite microspheres to form the thermosensitive inner shell. The phase transition temperature of 40°C to 45°C and the phase transition expansion rate of 15% to 20% mean that the thermosensitive inner shell can accurately match the characteristic temperature of the accelerated hydration period of C3S, providing sufficient driving force for the cracking of the rigid outer shell through phase transition expansion.
[0043] Specifically, at room temperature (below 40°C), since the temperature does not reach the phase change expansion trigger temperature of the thermosensitive inner shell, the thermosensitive inner shell will not undergo phase change expansion, and the double-layer shell maintains effective encapsulation of the C3S hydration-targeted core material, and the thermosensitive controlled-release microcapsule maintains structural integrity. When cement enters the accelerated hydration period of C3S, the system temperature rises to 40°C to 45°C, reaching the phase change expansion trigger temperature of the thermosensitive inner shell. In the polyethylene glycol / silica composite microspheres constituting the thermosensitive outer shell, polyethylene glycol undergoes endothermic melting from a crystalline solid state. The molecular chains transform into a highly elastic state, changing from ordered folding to disordered expansion, increasing the intermolecular distance. Under the condition that the rigid silica framework constrains the C3S hydration-targeted control core material to prevent leakage but allows for volume expansion, a volume expansion of 15% to 20% occurs. This leads to the overall volume expansion of the temperature-sensitive expansion shell, generating directional physical extrusion force that precisely breaks through the dense structure of the rigid shell. This causes the double-layer shell of the temperature-sensitive controlled-release microcapsule to crack uniformly, achieving timed, quantitative, and precise release of the C3S hydration-targeted control core material, and targeting the accelerated hydration period of C3S.
[0044] The polyethylene glycol / silica composite microspheres used in this invention are from Beijing Zhongke Keyou Technology Co., Ltd.
[0045] In one specific embodiment of the present invention, the polyethylene glycol / silica composite microspheres are surface-modified with a silane coupling agent. The surface of the silane-modified polyethylene glycol / silica composite microspheres contains amino active groups, which can form chemical bonds with the C3S hydration-targeting core material, achieving directional coating of the C3S hydration-targeting core material. It should be noted that excessive residual silane coupling agent on the surface of the silane-modified polyethylene glycol / silica composite microspheres should be avoided, as this not only increases the preparation cost but may also potentially adversely affect the workability of concrete using the temperature-sensitive controlled-release microcapsules.
[0046] In one specific embodiment of the present invention, the polyethylene glycol / silica composite microspheres are surface modified with a silane coupling agent according to the following steps: The polyethylene glycol / silica composite microspheres were immersed in a silane coupling agent solution and stirred to react, thereby completing the silane coupling agent surface modification of the polyethylene glycol / silica composite microspheres.
[0047] In one specific embodiment of the present invention, the solvent in the silane coupling agent solution is considered to be 100% by mass, wherein the mass fraction of the silane coupling agent is 2wt% to 7wt%, preferably 2wt% to 5wt%; the mass ratio of the polyethylene glycol / silica composite microspheres to the silane coupling agent solution is 1:5. The mass fraction of the silane coupling agent in the silane coupling agent solution and the mass ratio of the polyethylene glycol / silica composite microspheres to the silane coupling agent solution are limited as described above to ensure that the polyethylene glycol / silica composite microspheres receive sufficient surface modification from the silane coupling agent, while avoiding the potential adverse effects of excessive silane coupling agent.
[0048] In a preferred embodiment of the present invention, the silane coupling agent is γ-aminopropyltriethoxysilane, namely KH-550.
[0049] In one specific embodiment of the present invention, the silane coupling agent solution is an alcoholic solution of the silane coupling agent, preferably an ethanolic solution of the silane coupling agent.
[0050] In one specific embodiment of the present invention, the stirring reaction used for surface modification of the silane coupling agent is carried out at a temperature of 30°C for a duration of 2 hours.
[0051] In one specific embodiment of the present invention, the reaction system obtained after the stirring reaction is separated into solid and liquid phases, the solid phase is collected and dried to obtain the polyethylene glycol / silica composite microspheres modified with silane coupling agent, which are used to prepare the thermosensitive body inner shell; wherein the drying condition is vacuum drying at 50°C to constant weight.
[0052] In one specific embodiment of the present invention, the rigid outer shell is a mixture of calcium silicate gel and polyethylene glycol. The silanol groups of the calcium silicate gel are capable of dehydration condensation, and the terminal hydroxyl groups of the polyethylene glycol and the silanol groups of the calcium silicate gel are capable of co-condensation. Combined with the synergistic crosslinking of the residual silane coupling agent in the thermosensitive inner shell, an inorganic-organic interpenetrating network structure is formed. This makes the rigid outer shell more dense, effectively encapsulating the thermosensitive inner shell and the C3S hydration-targeted core material, giving the thermosensitive controlled-release microcapsule good mechanical strength, maintaining structural integrity below 40°C, and preventing undesirable release of the C3S hydration-targeted core material (e.g., misrelease, premature release).
[0053] In one specific embodiment of the present invention, the mass ratio of the calcium silicate gel to the polyethylene glycol in the rigid shell is 2:1.
[0054] In one specific embodiment of the present invention, the calcium silicate gel is granular with a particle size of 20 μm to 40 μm. The calcium silicate gel used in the present invention is obtained from the recovery of cement hydration byproducts, which not only has excellent compatibility with cement systems but also realizes resource recycling.
[0055] In a preferred embodiment of the present invention, the polyethylene glycol in the rigid shell is polyethylene glycol 400.
[0056] In one specific embodiment of the present invention, the particle size of the temperature-sensitive controlled-release microcapsules is ≤75μm.
[0057] A second aspect of the present invention provides a method for preparing temperature-sensitive controlled-release microcapsules as described in the first aspect of the present invention, comprising the following steps: After preparing the C3S hydration-targeted regulation core material into a first emulsion, the temperature-sensitive body inner shell is wrapped around the surface of the emulsion droplet to obtain a single-shell capsule. The rigid outer shell is further wrapped around the surface of the single-shell capsule to produce the temperature-sensitive controlled-release microcapsule.
[0058] In one specific embodiment of the present invention, the method includes: S1, the modified polycarboxylic acid ether ester, emulsifier and water are mixed and emulsified to obtain the first emulsion; S2, mix the polyethylene glycol / silica composite microspheres and the first emulsion, adjust the pH, and stir to coat the polyethylene glycol / silica composite microspheres on the surface of the emulsion droplets to form the thermosensitive body swollen inner shell, and obtain the second emulsion containing the single-shell capsule; S3, the calcium silicate gel and polyethylene glycol are prepared into a sol, which is then dropped into the stirred second emulsion to react, so that the sol is deposited on the surface of the single-shell capsule to obtain a first suspension containing a double-shell capsule; S4, mix anhydrous ethanol and the first suspension to crosslink and solidify the sol on the surface of the double-shell capsule to form the rigid outer shell, and obtain a second suspension containing the temperature-sensitive controlled-release microcapsules.
[0059] In one specific embodiment of the present invention, in step S1, the modified polycarboxylic acid ether ester is dissolved in water, the emulsifier is added, and the mixture is stirred to dissolve the emulsifier and complete the emulsification to obtain the first emulsion.
[0060] In one specific embodiment of the present invention, in step S1, the mass ratio of the modified polycarboxylic acid ether ester to water is 1:4.
[0061] In one specific embodiment of the present invention, the emulsifier is an anionic surfactant, preferably sodium dodecylbenzenesulfonate (SDBS).
[0062] In one specific embodiment of the present invention, in step S1, the total mass of the modified polycarboxylic acid ether ester and water is 100%, and the amount of emulsifier added is 0.3 wt%.
[0063] In one specific embodiment of the present invention, in step S2, the polyethylene glycol / silica composite microspheres are first surface-modified with a silane coupling agent, and then mixed with the first emulsion. The specific method and steps for surface modification of the polyethylene glycol / silica composite microspheres with a silane coupling agent have been described in detail above and will not be repeated here.
[0064] In one specific embodiment of the present invention, in step S2, the polyethylene glycol / silica composite microspheres are added to the first emulsion, the pH is adjusted, and the mixture is stirred to allow the polyethylene glycol / silica composite microspheres to be directionally coated on the surface of the emulsion droplets through chemical bonding and physical adsorption, forming the thermosensitive inner shell, thus obtaining a second emulsion containing the single-shell capsule. The emulsion droplets in the first emulsion are essentially droplets containing the modified polycarboxylic acid ether ester.
[0065] In this invention, in step S2 above, the polyethylene glycol / silica composite microspheres, after being modified with a silane coupling agent, have amino active groups on their surface, which can form chemical bonds with the modified polycarboxylic acid ether ester. Furthermore, there is a physical adsorption relationship between the polyethylene glycol / silica composite microspheres and the modified polycarboxylic acid ether ester. Therefore, they can be directionally coated on the surface of droplets containing the modified polycarboxylic acid ether ester through chemical bonding and physical adsorption, forming regular single-shell capsules.
[0066] In one specific embodiment of the present invention, the pH is adjusted to 7.5 to 8.5 to provide a suitable environment for the directional coating of the emulsion droplets by the polyethylene glycol / silica composite microspheres.
[0067] In one specific embodiment of the present invention, in step S2, the stirring speed for directional coating of the emulsion droplets by the polyethylene glycol / silica composite microspheres is preferably 800 r / min, and the stirring time is preferably 40 min. Under these stirring conditions, it is beneficial for the polyethylene glycol / silica composite microspheres to uniformly and directionally coat the surface of the emulsion droplets, forming a uniformly thick thermosensitive inner shell.
[0068] In one specific embodiment of the present invention, the calcium silicate gel and polyethylene glycol are prepared into a sol according to the following steps: The calcium silicate gel, the polyethylene glycol, and water are mixed and stirred to obtain a homogeneous sol.
[0069] In one specific embodiment of the present invention, in step S3, the mass ratio of the calcium silicate gel to the polyethylene glycol is 2:1, and the mass ratio of the total mass of the calcium silicate gel and the polyethylene glycol to the mass of water is 1:3.
[0070] In one specific embodiment of the present invention, in step S3, the stirring speed for preparing the sol is 500 r / min and the stirring time is 20 min.
[0071] In one specific embodiment of the present invention, the sol is slowly dripped into the second emulsion while it is being stirred; after the sol has been added, stirring continues to carry out the reaction, so that the sol is uniformly deposited on the surface of the single-shell capsule, thereby transforming the single-shell capsule into a double-shell capsule.
[0072] In one specific embodiment of the present invention, during the dropwise addition of the sol, the second emulsion is stirred at a rotation speed of 500 r / min; the dropwise addition rate of the sol is 3 mL / min to 5 mL / min.
[0073] In one specific embodiment of the present invention, the reaction conditions after the sol is added include: stirring at 500 r / min for 2.5 h at 30±2 °C.
[0074] In one specific embodiment of the present invention, anhydrous ethanol is added to the first suspension, and the mixture is stirred to crosslink and solidify the sol on the surface of the bishell capsule. The mixture is then allowed to stand and age to form a dense, rigid outer shell, resulting in a second suspension containing the temperature-sensitive controlled-release microcapsules. Here, the sol crosslinking and solidification essentially involves the dehydration condensation of the silanol groups in the calcium silicate gel and the co-condensation of the terminal hydroxyl groups of the polyethylene glycol with the silanol groups in the calcium silicate gel. Combined with the synergistic crosslinking of the residual silane coupling agent in the inner shell of the temperature-sensitive capsule, a dense, rigid inorganic-organic interpenetrating network structure is formed.
[0075] In one specific embodiment of the present invention, the mass of the first suspension is 100%, and the amount of anhydrous ethanol added is 1 wt%.
[0076] In one specific embodiment of the present invention, the stirring time for the purpose of cross-linking and solidifying the sol on the surface of the double-shell capsule is 10 min; the standing aging time is 1 h.
[0077] In one specific embodiment of the present invention, steps S1, S2 (excluding the silane coupling agent surface modification of the polyethylene glycol / silica composite microspheres) and S4 are all performed at room temperature.
[0078] In one specific embodiment of the present invention, the method further includes: S5, the second suspension is separated into solid and liquid phases, the solid phase is collected, dried and post-processed to obtain the temperature-sensitive controlled-release microcapsules.
[0079] In one specific embodiment of the present invention, the second suspension is subjected to solid-liquid separation by vacuum filtration.
[0080] In one specific embodiment of the present invention, the filter cake obtained by vacuum filtration is dried to constant weight, wherein the drying conditions are vacuum drying at 50±2℃ to constant weight.
[0081] In one specific embodiment of the present invention, the post-processing includes grinding and passing through a 200-mesh standard sieve to obtain the temperature-sensitive controlled-release microcapsules in powder form.
[0082] In one specific embodiment of the present invention, the amount of modified polycarboxylic acid ether ester is 60-70 parts by weight, the amount of polyethylene glycol / silica composite microspheres is 20-30 parts by weight, and the total amount of calcium silicate gel and polyethylene glycol is 10-18 parts by weight; preferably, the amount of modified polycarboxylic acid ether ester is 60-70 parts by weight, the amount of polyethylene glycol / silica composite microspheres is 20-25 parts by weight, and the total amount of calcium silicate gel and polyethylene glycol is 10-15 parts by weight. The main process of the method for preparing the thermosensitive controlled-release microcapsules provided by the present invention includes aqueous emulsification coating, sol deposition, and ethanol crosslinking and curing. The process is mild, with minimal material loss, and the feeding ratio is basically consistent with the component ratio of the finished product. Therefore, with the feeding ratio of "60-70 parts by mass of the modified polycarboxylic acid ether ester, 20-30 parts by mass of the polyethylene glycol / silica composite microspheres, and 10-18 parts by mass of the total amount of the calcium silicate gel and the polyethylene glycol", the thermosensitive controlled-release microcapsules containing "60-70 parts by mass of the C3S hydration-targeting regulating core material, 20-30 parts by mass of the thermosensitive inner shell, and 10-18 parts by mass of the rigid outer shell" can be prepared.
[0083] The third aspect of the present invention provides the application of the temperature-sensitive controlled-release microcapsules according to the first aspect of the present invention or the temperature-sensitive controlled-release microcapsules prepared by the method according to the second aspect of the present invention in the control of temperature rise during cement hydration.
[0084] In one specific embodiment of the present invention, the application includes: adding the temperature-sensitive controlled-release microcapsules to mass concrete to regulate the temperature rise during cement hydration. As described above, the temperature-sensitive controlled-release microcapsules are in powder form with a particle size ≤75μm, and in field application, they can be directly dry-mixed uniformly with cement, mineral admixtures, and aggregates.
[0085] In one specific embodiment of the present invention, the dosage of the temperature-sensitive controlled-release microcapsules is 0.8wt% to 2.0wt% of the mass of the cementitious materials in the concrete.
[0086] In a preferred embodiment of the present invention, the dosage of the temperature-sensitive controlled-release microcapsules is 0.8 wt% to 1.2 wt% of the mass of the cementitious materials in the concrete.
[0087] As is known to those skilled in the art, the “cementing materials” mentioned herein include materials added to concrete that have the ability to bind and hydrate when exposed to water, such as cement, silica fume, and fly ash.
[0088] The following provides several embodiments and comparative examples, along with performance tests, to further detail the technical solution and the technical effects achieved by the present invention.
[0089] The modified polycarboxylic acid ether ester used below is from Tianjin Rumi Jiyue New Materials Co., Ltd. The number average molecular weight of the modified polycarboxylic acid ether ester is 10,000. It is prepared by grafting maleic anhydride onto polycarboxylic acid water-reducing agent and has a selective inhibition rate of 45%.
[0090] The polyethylene glycol / silica composite microspheres used below are from Beijing Zhongke Keyou Technology Co., Ltd., with a particle size of 60μm, a phase transition temperature of 40℃ to 45℃, and a phase change expansion rate of 18%.
[0091] The following cement was used: P, from Jinyu Group. O 42.5R cement, P I 52.5 cement, P S 42.5R cement, P F 32.5R cement.
[0092] The calcium silicate gel used below has a particle size of 30 μm, and the polyethylene glycol (used to form a rigid shell, to distinguish it from the polyethylene glycol in the polyethylene glycol / silica composite microspheres) is PEG-400.
[0093] The silane coupling agent used below is KH-550.
[0094] The emulsifier used below is sodium dodecylbenzenesulfonate (SDBS).
[0095] Unless otherwise specified, all raw materials used in this invention are commercially available.
[0096] Preparation of thermosensitive controlled-release microcapsules.
[0097] All parts referred to below are parts by weight.
[0098] Example 1: Step 1: Surface modification of polyethylene glycol / silica composite microspheres with silane coupling agent: Take 22 parts of polyethylene glycol / silica composite microspheres, add 110 parts of 3wt% KH-550 ethanol solution, stir at 30℃ for 2h, and then vacuum dry at 50℃ to constant weight to obtain modified temperature-sensitive microspheres. Step 2, preparation of single-shell capsules: Dissolve 65 parts of modified polycarboxylic acid ether ester in 260 parts of deionized water, add 0.975 parts of SDBS, stir and dissolve to obtain the first emulsion; add the modified thermosensitive microspheres prepared in step 1 to the first emulsion, adjust the pH of the system to 8.0 with 0.1 mol / L NaOH solution, stir at 800 r / min for 40 min, so that the polyethylene glycol / silica composite microspheres are coated on the surface of the emulsion droplets to form a thermosensitive inner shell, and obtain the second emulsion containing single-shell capsules; Step 3, preparation of composite wall material sol: Dissolve 8.67 parts of calcium silicate gel and 4.33 parts of PEG-400 in 39 parts of deionized water, stir at 500 r / min for 20 min to obtain composite wall material sol; Step 4, preparation of double-shell capsules: The composite wall material sol obtained in step 3 is added dropwise at 4 mL / min to the second emulsion containing single-shell capsules obtained in step 2, stirred at 500 r / min, and reacted at 30℃ for 2.5 h to allow the sol to deposit on the surface of the single-shell capsules, thus obtaining the first suspension containing double-shell capsules. Step 5, composite wall material curing: Add 0.533 parts of anhydrous ethanol (1 wt% of the mass of the first suspension) to the first suspension containing double-shell capsules obtained in step 4, stir for 10 min to cross-link and solidify the sol on the surface of the double-shell capsules to form a rigid shell, and then age for 1 h to make the rigid shell dense, to obtain the second suspension containing temperature-sensitive controlled-release microcapsules. Step 6, Drying and Grinding: The second suspension containing temperature-sensitive controlled-release microcapsules obtained in Step 5 is filtered, the filter cake is collected and dried under vacuum at 50°C to constant weight, and then ground through a 200-mesh sieve to obtain powdered temperature-sensitive controlled-release microcapsules with a particle size ≤75μm. This is a cement hydration temperature rise control material, hereinafter referred to as "control material".
[0099] Example 1.1: Step 1: Surface modification of polyethylene glycol / silica composite microspheres with silane coupling agent: Take 30 parts of polyethylene glycol / silica composite microspheres, add 150 parts of 3wt% KH-550 ethanol solution, stir at 30℃ for 2h, and then vacuum dry at 50℃ to constant weight to obtain modified temperature-sensitive microspheres. Step 2, preparation of single-shell capsules: Dissolve 65 parts of modified polycarboxylic acid ether ester in 260 parts of deionized water, add 0.975 parts of SDBS, stir and dissolve to obtain the first emulsion; add the modified thermosensitive microspheres prepared in step 1 to the first emulsion, adjust the pH of the system to 8.0 with 0.1 mol / L NaOH solution, stir at 800 r / min for 40 min, so that the polyvinyl alcohol / silica composite microspheres are coated on the surface of the emulsion droplets to form a thermosensitive inner shell, and obtain the second emulsion containing single-shell capsules; Step 3, preparation of composite wall material sol: Dissolve 8.67 parts of calcium silicate gel and 4.33 parts of PEG-400 in 39 parts of deionized water, stir at 500 r / min for 20 min to obtain composite wall material sol; Step 4, preparation of double-shell capsules: The composite wall material sol obtained in step 3 is added dropwise at 4 mL / min to the second emulsion containing single-shell capsules obtained in step 2, stirred at 500 r / min, and reacted at 30℃ for 2.5 h to allow the sol to deposit on the surface of the single-shell capsules, thus obtaining the first suspension containing double-shell capsules. Step 5, composite wall material curing: Add anhydrous ethanol (1 wt% of the mass of the first suspension) to the first suspension containing double-shell capsules obtained in step 4, stir for 10 min to crosslink and solidify the sol on the surface of the double-shell capsules to form a rigid shell, and then age for 1 h to make the rigid shell dense, to obtain the second suspension containing temperature-sensitive controlled-release microcapsules. Step 6, Drying and Grinding: The second suspension containing temperature-sensitive controlled-release microcapsules obtained in Step 5 is filtered, the filter cake is collected and dried under vacuum at 50°C to constant weight, and then ground through a 200-mesh sieve to obtain powdered temperature-sensitive controlled-release microcapsules with a particle size ≤75μm. This is a cement hydration temperature rise control material, hereinafter referred to as "control material".
[0100] Example 1.2: Step 1: Surface modification of polyethylene glycol / silica composite microspheres with silane coupling agent: Take 22 parts of polyethylene glycol / silica composite microspheres, add 110 parts of 3wt% KH-550 ethanol solution, stir at 30℃ for 2h, and then vacuum dry at 50℃ to constant weight to obtain modified temperature-sensitive microspheres. Step 2, preparation of single-shell capsules: Dissolve 65 parts of modified polycarboxylic acid ether ester in 260 parts of deionized water, add 0.975 parts of SDBS, stir and dissolve to obtain the first emulsion; add the modified thermosensitive microspheres prepared in step 1 to the first emulsion, adjust the pH of the system to 8.0 with 0.1 mol / L NaOH solution, stir at 800 r / min for 40 min, so that the polyvinyl alcohol / silica composite microspheres are coated on the surface of the emulsion droplets to form a thermosensitive inner shell, and obtain the second emulsion containing single-shell capsules; Step 3, preparation of composite wall material sol: Dissolve 12 parts calcium silicate gel and 6 parts PEG-400 in 54 parts deionized water, stir at 500 r / min for 20 min to obtain composite wall material sol; Step 4, preparation of double-shell capsules: The composite wall material sol obtained in step 3 is added dropwise at 4 mL / min to the second emulsion containing single-shell capsules obtained in step 2, stirred at 500 r / min, and reacted at 30℃ for 2.5 h to allow the sol to deposit on the surface of the single-shell capsules, thus obtaining the first suspension containing double-shell capsules. Step 5, composite wall material curing: Add anhydrous ethanol (1 wt% of the mass of the first suspension) to the first suspension containing double-shell capsules obtained in step 4, stir for 10 min to crosslink and solidify the sol on the surface of the double-shell capsules to form a rigid shell, and then age for 1 h to make the rigid shell dense, to obtain the second suspension containing temperature-sensitive controlled-release microcapsules. Step 6, Drying and Grinding: The second suspension containing temperature-sensitive controlled-release microcapsules obtained in Step 5 is filtered, the filter cake is collected and dried under vacuum at 50°C to constant weight, and then ground through a 200-mesh sieve to obtain powdered temperature-sensitive controlled-release microcapsules with a particle size ≤75μm. This is a cement hydration temperature rise control material, hereinafter referred to as "control material".
[0101] Example 1.3: Step 1: Surface modification of polyethylene glycol / silica composite microspheres with silane coupling agent: Take 22 parts of polyethylene glycol / silica composite microspheres, add 110 parts of KH-550 ethanol solution with a mass fraction of 7wt%, stir at 30℃ for 2h, and then vacuum dry at 50℃ to constant weight to obtain modified temperature-sensitive microspheres. Step 2, preparation of single-shell capsules: Dissolve 65 parts of modified polycarboxylic acid ether ester in 260 parts of deionized water, add 0.975 parts of SDBS, stir and dissolve to obtain the first emulsion; add the modified thermosensitive microspheres prepared in step 1 to the first emulsion, adjust the pH of the system to 8.0 with 0.1 mol / L NaOH solution, stir at 800 r / min for 40 min, so that the polyvinyl alcohol / silica composite microspheres are coated on the surface of the emulsion droplets to form a thermosensitive inner shell, and obtain the second emulsion containing single-shell capsules; Step 3, preparation of composite wall material sol: Dissolve 8.67 parts of calcium silicate gel and 4.33 parts of PEG-400 in 39 parts of deionized water, stir at 500 r / min for 20 min to obtain composite wall material sol; Step 4, preparation of double-shell capsules: The composite wall material sol obtained in step 3 is added dropwise at 4 mL / min to the second emulsion containing single-shell capsules obtained in step 2, stirred at 500 r / min, and reacted at 30℃ for 2.5 h to allow the sol to deposit on the surface of the single-shell capsules, thus obtaining the first suspension containing double-shell capsules. Step 5, composite wall material curing: Add anhydrous ethanol (1 wt% of the mass of the first suspension) to the first suspension containing double-shell capsules obtained in step 4, stir for 10 min to crosslink and solidify the sol on the surface of the double-shell capsules to form a rigid shell, and then age for 1 h to make the rigid shell dense, to obtain the second suspension containing temperature-sensitive controlled-release microcapsules. Step 6, Drying and Grinding: The second suspension containing temperature-sensitive controlled-release microcapsules obtained in Step 5 is filtered, the filter cake is collected and dried under vacuum at 50°C to constant weight, and then ground through a 200-mesh sieve to obtain powdered temperature-sensitive controlled-release microcapsules with a particle size ≤75μm. This is a cement hydration temperature rise control material, hereinafter referred to as "control material".
[0102] Example 2: Step 1: Surface modification of polyethylene glycol / silica composite microspheres with silane coupling agent: Take 20 parts of polyethylene glycol / silica composite microspheres, add 100 parts of 3wt% KH-550 ethanol solution, stir at 30℃ for 2h, and then vacuum dry at 50℃ to constant weight to obtain modified temperature-sensitive microspheres. Step 2, preparation of single-shell capsules: Dissolve 60 parts of modified polycarboxylic acid ether ester in 240 parts of deionized water, add 0.9 parts of SDBS, stir and dissolve to obtain the first emulsion; add the modified thermosensitive microspheres prepared in step 1 to the first emulsion, adjust the pH of the system to 8.0 with 0.1 mol / L NaOH solution, stir at 800 r / min for 40 min, so that the polyvinyl alcohol / silica composite microspheres are coated on the surface of the emulsion droplets to form a thermosensitive inner shell, and obtain the second emulsion containing single-shell capsules; Step 3, preparation of composite wall material sol: Dissolve 10 parts calcium silicate gel and 5 parts PEG-400 in 45 parts deionized water, stir at 500 r / min for 20 min to obtain composite wall material sol; Step 4, preparation of double-shell capsules: The composite wall material sol obtained in step 3 is added dropwise at 4 mL / min to the second emulsion containing single-shell capsules obtained in step 2, stirred at 500 r / min, and reacted at 30℃ for 2.5 h to allow the sol to deposit on the surface of the single-shell capsules, thus obtaining the first suspension containing double-shell capsules. Step 5, composite wall material curing: Add anhydrous ethanol (1 wt% of the mass of the first suspension) to the first suspension containing double-shell capsules obtained in step 4, stir for 10 min to crosslink and solidify the sol on the surface of the double-shell capsules to form a rigid shell, and then age for 1 h to make the rigid shell dense, to obtain the second suspension containing temperature-sensitive controlled-release microcapsules. Step 6, Drying and Grinding: The second suspension containing temperature-sensitive controlled-release microcapsules obtained in Step 5 is filtered, the filter cake is collected and dried under vacuum at 50°C to constant weight, and then ground through a 200-mesh sieve to obtain powdered temperature-sensitive controlled-release microcapsules with a particle size ≤75μm. This is a cement hydration temperature rise control material, hereinafter referred to as "control material".
[0103] Example 3: Step 1: Surface modification of polyethylene glycol / silica composite microspheres with silane coupling agent: Take 25 parts of polyethylene glycol / silica composite microspheres, add 125 parts of 3wt% KH-550 ethanol solution, stir at 30℃ for 2h, and then vacuum dry at 50℃ to constant weight to obtain modified temperature-sensitive microspheres. Step 2, preparation of single-shell capsules: Dissolve 70 parts of modified polycarboxylic acid ether ester in 280 parts of deionized water, add 1.05 parts of SDBS, stir to dissolve, and obtain the first emulsion; add the modified thermosensitive microspheres prepared in step 1 to the first emulsion, adjust the pH of the system to 8.0 with 0.1 mol / L NaOH solution, stir at 800 r / min for 40 min, so that the polyvinyl alcohol / silica composite microspheres are coated on the surface of the emulsion droplets to form a thermosensitive inner shell, and obtain the second emulsion containing single-shell capsules; Step 3, preparation of composite wall material sol: Dissolve 6.67 parts of calcium silicate gel and 3.33 parts of PEG-400 in 30 parts of deionized water, stir at 500 r / min for 20 min to obtain composite wall material sol; Step 4, preparation of double-shell capsules: The composite wall material sol obtained in step 3 is added dropwise at 4 mL / min to the second emulsion containing single-shell capsules obtained in step 2, stirred at 500 r / min, and reacted at 30℃ for 2.5 h to allow the sol to deposit on the surface of the single-shell capsules, thus obtaining the first suspension containing double-shell capsules. Step 5, composite wall material curing: Add anhydrous ethanol (1 wt% of the mass of the first suspension) to the first suspension containing double-shell capsules obtained in step 4, stir for 10 min to crosslink and solidify the sol on the surface of the double-shell capsules to form a rigid shell, and then age for 1 h to make the rigid shell dense, to obtain the second suspension containing temperature-sensitive controlled-release microcapsules. Step 6, Drying and Grinding: The second suspension containing temperature-sensitive controlled-release microcapsules obtained in Step 5 is filtered, the filter cake is collected and dried under vacuum at 50°C to constant weight, and then ground through a 200-mesh sieve to obtain powdered temperature-sensitive controlled-release microcapsules with a particle size ≤75μm. This is a cement hydration temperature rise control material, hereinafter referred to as "control material".
[0104] Test Example 1: This test case aims to evaluate the performance of the control materials prepared in Examples 1 to 3 in P The application effect of O 42.5R cement in mass concrete, specifically in terms of "P" The basic formula of "O 42.5R cement mass concrete" was used as the blank group, and "P" was used as the basis for the formula. A certain proportion of modifier material was added to the basic formula of "O 42.5R cement mass concrete" as the test group. Multiple performance tests were conducted on both the control group and the test group. The technical indicators used were peak hydration temperature rise, peak duration, total heat release of cement over 7 days, initial setting time, final setting time, 1-day compressive strength, 7-day compressive strength, and 28-day compressive strength. The modifier material prepared in Examples 1 to 3 was evaluated in terms of P... The application effect of O 42.5R cement in mass concrete was tested in the following way.
[0105] (1) P Basic formula for O 42.5R cement mass concrete: P The cementitious material system consists of 245 kg of O 42.5R cement and 105 kg of Grade II fly ash, with a total mass of 350 kg. The Grade II fly ash accounts for 30 wt% of the total cementitious material. 760 kg of medium sand with a fineness modulus of 2.6 to 2.8 and a mud content ≤2 wt% and 1080 kg of crushed stone with a continuous gradation of 5 to 25 mm and a needle-like / flaky content ≤8 wt% are selected. The mixing water is 140 kg, and the water-cement ratio is controlled at 0.4. Simultaneously, 0.7 kg of standard polycarboxylate superplasticizer, calculated at 0.2 wt% of the total cementitious material mass, is added. The basic formula has a sand ratio of approximately 41.3% and a unit concrete density of approximately 2330.7 kg / m³, which meets the workability, density, and strength development requirements for large-volume concrete construction.
[0106] (2) Experimental grouping: P provided in (1) The basic formula for O 42.5R cement mass concrete is a blank group; P provided in (1) The basic formula of O 42.5R cement mass concrete was supplemented with the control materials prepared in Examples 1 to 3, calculated at 1.5wt% of the total mass of cementitious materials, with a single admixture of 5.25kg, as experimental groups 1-1, 2-1, and 3-1. P provided in (1) The control material prepared in Example 1, calculated at 1.0 wt% of the total mass of cementitious materials, was added to the basic formula of O 42.5R cement-mass concrete, with a single admixture amount of 3.5 kg, and was used as test groups 1-2.
[0107] (3) P Performance testing of O 42.5R cement mass concrete: According to the provisions of the "Test Procedures for Cement and Cement Concrete in Highway Engineering" (JTG 3420-2020), "Test Methods for Standard Consistency Water Requirement, Setting Time and Soundness of Cement" (GB / T 1346 2024), "Test Methods for Heat of Hydration of Cement" (GB / T12959-2024), and "Standard for Test Methods of Physical and Mechanical Properties of Ordinary Concrete" (GB / T50081-2019), the peak hydration temperature rise, peak duration, total heat release of cement over 7 days, initial setting time, final setting time, 1-day compressive strength, 7-day compressive strength, and 28-day compressive strength of the blank group and test groups 1-1, 2-1, 3-1, and 1-2 in (2) were measured respectively. The change rate of total heat release of cement over 7 days relative to the blank group was calculated. The results are shown in Table 1.
[0108] Table 1. P values of the blank group and the experimental group Performance test results of O 42.5R cement mass concrete.
[0109]
[0110] As shown in Table 1, the peak hydration temperature rise of experimental groups 1-1 to 3-1 and 1-2 was 9 to 11℃ lower than that of the control group (the hydration temperature rise reduction rate was 13.24% to 16.18%), the duration of the temperature peak was extended by 20 to 23 hours compared with the control group (i.e., the temperature peak broadened by 20 to 23 hours), the total heat release at 7 days was only 1.69% to 2.25% lower than that of the control group, and the extension of the final setting time and initial setting time compared with the control group was less than 1 hour. There was no significant decrease in compressive strength at 1 day, 7 days, and 28 days.
[0111] This indicates that the controlled-release material (i.e., temperature-sensitive controlled-release microcapsules) prepared in this invention can achieve targeted control of the accelerated hydration period of C3S with high selectivity without affecting its final hydration degree, and does not interfere with the hydration of other minerals such as C3A, C4AF, and C2S. It achieves excellent temperature peak control effects such as reduced temperature rise and broadened temperature peak, while avoiding a significant extension of the initial and final setting times, thus ensuring workability, and also improving the compressive strength of large-volume concrete at all ages.
[0112] Test Example 2: This test case aims to evaluate the effect of the control material provided by this invention on P. The influence of O 42.5R cement on the long-term strength and durability of mass concrete was investigated. Specifically, the 90-day long-term compressive strength, impermeability grade, crack resistance index (a core durability indicator of mass concrete), and frost resistance grade (rapid freezing method) of concrete were tested on the blank group and experimental group 1-1 in Test Example 1. Based on the changes in 90-day long-term compressive strength, impermeability grade, crack resistance index, and frost resistance grade of experimental group 1-1 compared to the blank group, the effect of the control material on P was evaluated. The effects of O 42.5R cement on the long-term strength and durability of mass concrete are as follows.
[0113] According to the test grouping in Test Example 1 (2), a blank group and test group 1-1 were provided. Based on the provisions of the Standard Test Method for Physical and Mechanical Properties of Ordinary Concrete (GB / T50081-2019), the Standard Test Method for Long-Term Performance and Durability of Concrete (GB / T50082-2024), and the Guide for Durability Design and Construction of Concrete Structures (CCES 01-2004), the 90-day long-term compressive strength, impermeability grade, crack resistance index, and frost resistance grade of concrete in the blank group and test group 1-1 were tested. The results are shown in Table 2.
[0114] Table 2. 90-day long-term compressive strength, impermeability grade, crack resistance index of concrete in the blank group and test group 1-1 The results of the freeze resistance rating test.
[0115]
[0116] As shown in Table 2, the 90-day compressive strength of test group 1-1 maintained a retention rate of 99.66% compared to the blank group. Furthermore, due to the widening of the temperature peak (as confirmed by Table 1), the internal and external temperature difference was reduced, resulting in a 5.6% increase in the crack resistance index and an increase in the impermeability grade from W8 in the blank group to W9 in the test group 1-1. Moreover, the frost resistance grade of test group 1-1 was still maintained at the same F200 level as the blank group.
[0117] Although not listed in Table 2, the 90-day compressive strength, impermeability grade, and crack resistance index test results of test groups 2-1, 3-1, and 1-2 are actually comparable to those of test group 1-1.
[0118] This indicates that the control material provided by the present invention (i.e., temperature-sensitive controlled-release microcapsules) not only effectively controls the hydration temperature rise without adversely affecting the long-term strength of concrete, but also indirectly improves the durability of large-volume concrete in terms of crack resistance, impermeability, and freeze resistance, and has excellent compatibility with the concrete system.
[0119] Test Example 3: This test case aims to evaluate the adaptability of the control material provided by the present invention to high-temperature storage and extreme mixing environments in summer. Specifically, the control material prepared in Example 1 was added to P before and after high-temperature storage. The adaptability of the control material to high-temperature storage in summer was evaluated by using the change in hydration temperature after O 42.5R cement mass concrete. The control material prepared in Example 1 was added to P at different mixing temperatures. The setting time and peak temperature rise of O42.5R cement in mass concrete were used as indicators to evaluate the adaptability of control materials to extreme mixing environments.
[0120] I. High-temperature storage adaptability: The control material prepared in Example 1 was stored in a constant temperature and humidity environment of 40°C (to simulate extreme summer storage) for 90 days, and was recorded as sample A; The fresh regulatory material prepared in Example 1 was used as sample B; Sample A and Sample B were added to P at a ratio of 1.0 wt% of the total mass of cementitious materials. In the basic formula of O 42.5R cement mass concrete (P The basic formula for O 42.5R cement mass concrete is shown in “(1)” in Test Example 1. The peak hydration temperature rise, the duration of the temperature peak, the initial setting time and the final setting time were tested respectively. The test method was the same as that in Test Example 1. The results are shown in Table 3.
[0121] II. High-temperature mixing adaptability: The P recorded in "(1)" of test example 1 The temperature of the mixing water in the basic formula of O 42.5R cement mass concrete is controlled at 38℃, which is recorded as the high-temperature mixing blank group. In this high-temperature mixing blank group, the control material prepared in Example 1 was added at a ratio of 1.0 wt% of the total mass of cementitious materials, and this group was designated as the high-temperature mixing experimental group. The peak hydration temperature rise, duration of the temperature peak, initial setting time, and final setting time were tested for the high-temperature mixing blank group and the high-temperature mixing test group, respectively. The test method was the same as that for test example 1, and the results are shown in Table 3.
[0122] Table 3. Adaptability of control materials to high-temperature storage and extreme mixing environments in summer.
[0123]
[0124] As shown in Table 3, compared with sample B, the peak hydration temperature rise of sample A increased by only 1℃, the duration of the temperature peak was shortened by only 1h, and the initial setting time and final setting time were extended by only 0.1h. It can be seen that the control material provided by the present invention can still effectively control the hydration acceleration period of C3S after being stored in a high-temperature environment of 40℃ for 90 days. This indicates that the control material provided by the present invention has excellent room temperature storage stability and can adapt to high-temperature storage in summer without the risk of performance degradation. Compared with the high-temperature mixing blank group, the high-temperature mixing test group can still reduce the peak hydration temperature rise by 11°C, extend the duration of the temperature peak by 22 hours, and ensure that the initial setting time and final setting time are normal (both the initial setting time and final setting time are extended by less than 1 hour). It can be seen that the control material provided by the present invention can adapt well to the extreme working conditions of high-temperature mixing in summer.
[0125] Although not listed in Table 3, the test results of the hydration temperature rise peak, temperature peak duration, initial setting time, and final setting time of the control materials provided in Examples 2 and 3, respectively, measured according to the test steps of "Ⅰ, high temperature storage adaptability" and "Ⅱ, high temperature mixing adaptability", are actually comparable to the test results of Example 1 shown in Table 3.
[0126] In summary, the controlled-release material (i.e., temperature-sensitive controlled-release microcapsules) provided by this invention exhibits excellent adaptability to extreme working conditions such as high-temperature storage and high-temperature mixing in summer, meeting the requirements for large-volume concrete construction in summer.
[0127] Test Example 4: This test case aims to evaluate the universality of the control material provided by this invention for cement, specifically selecting "P" I 52.5, P S 42.5R, P Three types of silicate cement, "F 32.5R", were used, each with three water-cement ratios of "0.3 / 0.4 / 0.5" and two mineral admixtures of "(30% slag / 40% fly ash)", resulting in a total of 18 concrete formulations. The changes in "peak hydration temperature rise, duration of temperature rise, total heat release of cement over 7 days, initial setting time, final setting time, 1-day compressive strength, 7-day compressive strength, and 28-day compressive strength" before and after incorporating the modifier material prepared in Example 1 at 1.2 wt% of the total cementitious material mass in each concrete formulation were tested and compared. The effect of the modifier material prepared in Example 1 on "P" was evaluated. I 52.5, P S 42.5R, P The general applicability of the three types of silicate cement, F 32.5R, is as follows.
[0128] 1) The concrete formulas for Group 18 are shown in Table 4-1.
[0129] Table 4-1. Concrete formulations for the above 18 groups.
[0130]
[0131] 2) Concrete performance testing: For the concrete formulations of groups 1 to 18 shown in Table 4-1 in section 1), tests were conducted on "peak hydration temperature rise, duration of temperature rise, total heat release of cement over 7 days, initial setting time, final setting time, 1-day compressive strength, 7-day compressive strength, and 28-day compressive strength". The concrete formulations of groups 1 to 18 shown in Table 4-1 in 1) were added to the control material prepared in Example 1 at an addition ratio of 1.2wt% of the total mass of cementitious materials. Then, the peak hydration temperature rise, the duration of temperature rise, the total heat release of cement in 7 days, the initial setting time, the final setting time, the 1-day compressive strength, the 7-day compressive strength, and the 28-day compressive strength were tested respectively. The test methods for the above-mentioned "peak hydration temperature rise, duration of temperature rise, total heat release of cement over 7 days, initial setting time, final setting time, 1-day compressive strength, 7-day compressive strength, and 28-day compressive strength" are the same as those for Test Example 1, and the test results are shown in Table 4-2.
[0132] Table 4-2. Performance test results of the above 18 groups of concrete formulations before and after the addition of regulating materials.
[0133]
[0134] Table 4-2 shows that after adding the regulating materials to the concrete formulas of groups 1 to 18, the peak temperature rise of concrete hydration was reduced by about 10℃, the duration of the temperature peak was extended to more than 30 hours, the change rate of total heat release of cement over 7 days was less than 5%, the initial setting and final setting times were extended by less than 1 hour, and the compressive strength at each age did not decrease significantly.
[0135] It should be noted that when the control materials provided in Examples 2 and 3 were added to the concrete formulations of the above-mentioned groups 1 to 18 at an addition ratio of "1.2wt% of the total mass of cementitious materials", the test results of various properties were comparable to those in Example 1.
[0136] This indicates that the control material (i.e., temperature-sensitive controlled-release microcapsules) provided by the present invention has extremely strong universality, and its excitation target is minimally affected by raw materials and concrete mix proportions, making it widely adaptable to various large-volume concrete working conditions.
[0137] Test Example 5: This test case aims to evaluate the effect of adding different amounts of the control material provided by the present invention to P. The application effect of O 42.5R cement in mass concrete, specifically in terms of "P" The basic formula of "O 42.5R cement mass concrete" was used as the blank group, and "P" was used as the basis for the formula. Different proportions of modifiers were added to the basic formulation of "O 42.5R cement mass concrete" to form multiple test groups. Multiple performance tests were conducted on the control group and the test groups, using peak hydration temperature rise, peak duration, total heat release of cement over 7 days, initial setting time, final setting time, and 28-day compressive strength as technical indicators. The change rate of total heat release of cement over 7 days in the test groups relative to the control group was calculated. The modifiers prepared in Example 1 were evaluated by adding different dosages to P... The application effect of O 42.5R cement in mass concrete was tested in the following way.
[0138] i, P The basic formula for O 42.5R cement mass concrete is the same as that for test example 1.
[0139] ii. Experimental Groups: P provided in i The basic formula for O 42.5R cement mass concrete is a blank group; P provided in i The control material prepared in Example 1, calculated at 0.8wt%, 1.0wt%, and 2.0wt% of the total mass of cementitious materials, was added to the basic formula of O 42.5R cement-mass concrete, respectively, as experimental groups 5-1 to 5-3.
[0140] iii, P Performance testing of O 42.5R cement mass concrete: The peak hydration temperature rise, duration of the peak temperature, total heat release of cement over 7 days, initial setting time, final setting time, 1-day compressive strength, 7-day compressive strength, and 28-day compressive strength of the blank group and test groups 5-1 to 5-3 in test ii were measured respectively. The test methods were the same as those in test example 1. The change rate of total heat release of cement over 7 days of test groups 5-1 to 5-3 relative to the blank group was calculated. The results are shown in Table 5.
[0141] Table 5. P values of blank control group and experimental groups 5-1 to 5-3 Performance test results of O 42.5R cement mass concrete.
[0142]
[0143] As shown in Table 5, compared with the blank group, the experimental groups 5-1 to 5-3 with the added amount of controlled material of 0.8wt%, 1.0wt%, and 2.0wt% showed that the peak hydration temperature rise was reduced by 7 to 12℃, the duration of the temperature peak was extended to 32 to 36h, the change rate of total heat release in 7 days was 1.12% to 3.09%, the initial setting time and final setting time were extended by less than 1h, and the 28-day compressive strength retention rate was 99% to 99.6%.
[0144] This indicates that the control material provided by the present invention (i.e., temperature-sensitive controlled-release microcapsules) can effectively target and control the accelerated hydration period of C3S within the addition ratio of 0.8wt% to 2.0wt%, reduce the temperature peak, broaden the temperature peak without affecting the final degree of hydration, and do not interfere with the hydration of other minerals such as C3A, C4AF, and C2S. It can also ensure normal initial and final setting times and compressive strength with minimal attenuation. Furthermore, among experimental groups 5-1 to 5-3, although experimental group 5-1, with a control material addition of 0.8 wt%, achieved the lowest 7-day total heat release change rate, the smallest extension of initial and final setting times, and the best 28-day compressive strength, its control effect was not optimal (highest hydration temperature rise peak and shortest temperature peak duration); although experimental group 5-3, with a control material addition of 2.0 wt%, achieved the best control effect (lowest hydration temperature rise peak and longest temperature peak duration), its 28-day compressive strength was... The lowest strength, the largest change rate of total heat release over 7 days, and the longest extension of initial and final setting times were observed in the experimental group 5-2. In contrast, the peak hydration temperature rise of the group with 1.0 wt% of the regulating material decreased by only 9°C, with a temperature peak broadening by 22 hours. Furthermore, the change rate of total heat release over 7 days was moderate, the extension of initial and final setting times was moderate, and the 28-day compressive strength was not less than 52.0 MPa. This indicates that 1.0 wt% is the optimal dosage of the regulating material provided by this invention for large-volume concrete applications, achieving good regulating effects while also being economical. Of course, in practical applications, the dosage of the regulating material can be flexibly adjusted according to the specific temperature rise control requirements of the project.
[0145] It should be noted that the control materials provided in Examples 2 and 3 were added to the above-mentioned P at proportions of 0.8 wt%, 1.0 wt%, and 2.0 wt% of the total mass of the cementitious materials, respectively. After adding O 42.5R cement to the mass concrete foundation formula, the test results of various properties were comparable to those of Example 1 with the same admixture dosage.
[0146] Comparative Example 1: This comparative example provides a commercially available sodium gluconate as a material for controlling the temperature rise during cement hydration, hereinafter referred to as "controlling material".
[0147] Test Example 6: P provided in test example 1 (1) Add 1.0 wt% of the modifier provided in Comparative Example 1 (i.e., sodium gluconate) of the total mass of cementitious materials to the basic formula of O 42.5R cement mass concrete as test group 6-1. Following the same testing method as in Test Example 1, the peak hydration temperature rise, peak duration, total heat release of cement over 7 days, initial setting time, final setting time, and 1-day compressive strength of test group 6-1 were measured and compared with those of the blank group measured in Test Example 1. The change rate of total heat release of cement over 7 days in test group 6-1 relative to the blank group was calculated, and the results are shown in Table 6.
[0148] Table 6. P values of blank group and experimental group 6-1 Performance test results of O 42.5R cement mass concrete.
[0149]
[0150] Table 6 shows that, compared with the control group, the peak hydration temperature rise of experimental group 6-1 decreased by 8℃, the peak duration was only extended by 3h (the peak duration was only 15h), and the change rate of total heat release over 7 days was as high as 12.36%. This indicates that although sodium gluconate can reduce the peak hydration temperature rise, its effect on slowing down the peak is very poor, and it causes a significant decrease in total heat release. In addition, the initial and final setting times of experimental group 6-1 were extended by more than 10℃, and the 1-day compressive strength decreased to about 5MPa. This indicates that sodium gluconate also seriously prolongs the setting time of concrete and significantly reduces the early strength of concrete.
[0151] In other words, compared with the control material (i.e., temperature-sensitive controlled-release microcapsules) provided by the present invention, the sodium gluconate provided by Comparative Example 1 cannot reduce the peak temperature rise of hydration while slowing down the temperature peak, and cannot achieve normal total heat release. It even seriously affects the setting and strength development of concrete. As a cement hydration temperature rise control material, it has significant technical defects.
[0152] Comparative Example 2: This comparative example provides an organic-inorganic composite thermosensitive hydration heat regulation material purchased from Xi'an Ruixi Biotechnology. It is a typical existing thermosensitive material with ambient temperature as the trigger target and a phase transition temperature of 40℃. It is hereinafter referred to as "regulation material".
[0153] Test Example 7: P provided in test example 1 (1) The basic formulation of O 42.5R cement mass concrete was supplemented with 2.0 wt% of the total mass of cementitious materials provided in Comparative Example 2 (i.e., organic-inorganic composite temperature-sensitive hydration heat control material), which was used as experimental group 7-1. Following the same testing method as in Test Example 1, the peak hydration temperature rise, peak duration, total heat release of cement over 7 days, initial setting time, final setting time, and 28-day compressive strength of test group 7-1 were measured. These values were compared with those of the blank group and test group 1-1 measured in Test Example 1. The change rates of total heat release of cement over 7 days for test groups 7-1 and 1-1 relative to the blank group were calculated. The results are shown in Table 7.
[0154] Table 7. P values of blank group and experimental groups 7-1 and 1-1 Performance test results of O 42.5R cement mass concrete.
[0155]
[0156] As shown in Table 7, compared with the control group: Experimental group 7-1 reduced the peak hydration temperature rise by 6℃, broadened the temperature peak by 3h, and reduced the total heat release in 7 days by 9.83% (while experimental group 1-1 reduced the peak hydration temperature rise by 11℃, broadened the temperature peak by 23h, and reduced the total heat release in 7 days by 2.25%); Experimental group 7-1 extended the initial setting time and final setting time by 3h and 6.4h respectively (while experimental group 1-1 extended the initial setting time and final setting time by less than 1h); The 28-day compressive strength attenuation rate of experimental group 7-1 was as high as 7.3% (while the 28-day compressive strength attenuation rate of experimental group 1-1 was as low as 0.8%).
[0157] It is evident that the organic-inorganic composite temperature-sensitive hydration heat control material provided in Comparative Example 2 can only reduce the peak hydration temperature rise. However, since it uses ambient temperature as the single triggering target, it cannot effectively slow down the temperature peak. Furthermore, the ligand complexed calcium ions in the material cause the cement to fail to hydrate fully, resulting in a sharp drop in the total heat release and a significant decrease in the 28-day compressive strength.
[0158] Unlike the organic-inorganic composite temperature-sensitive hydration heat control material, the control material provided by this invention (i.e., temperature-sensitive controlled-release microcapsules) uses the accelerated hydration period of C3S as a precise trigger target. With only 1.5wt% of admixture (lower than the 2.0wt% admixture in experimental group 7-1), it can effectively broaden the temperature peak while reducing the hydration temperature rise, ensuring that the total heat release remains basically unchanged, and will not affect the normal setting of cement, ensuring normal strength development. This solves the core pain points of existing temperature-sensitive materials: "reduced total heat release, weak adaptability, and early delayed setting".
[0159] Comparative Example 3: This comparative example provides the same modified polycarboxylic acid ether ester as in Example 1 as a cement hydration temperature rise control material, hereinafter referred to as "control material".
[0160] Comparative Example 4: This comparative example provides the same polyethylene glycol / silica microspheres as those in Example 1 as a cement hydration temperature rise control material, hereinafter referred to as "control material".
[0161] Comparative Example 5: This comparative example provides a mixed powder of calcium silicate gel and PEG-400 as a cement hydration temperature rise control material, hereinafter referred to as "control material"; wherein, the mass ratio of calcium silicate gel, PEG-400, and calcium silicate gel and PEG-400 is the same as in Example 1.
[0162] Test Example 8: P provided in test example 1 (1) The modifier provided in Comparative Example 3 (i.e., modified polycarboxylate ether ester) was added to the basic formulation of O 42.5R cement mass concrete at a total mass of 1.5 wt% of cementitious materials as experimental group 8-1. P provided in test example 1 (1) The control material provided in Comparative Example 4 (i.e., polyethylene glycol / silica microspheres) was added at 1.5 wt% of the total mass of cementitious materials to the basic formula of O 42.5R cement mass concrete as experimental group 8-2. P provided in test example 1 (1) The control material provided in Comparative Example 5 (i.e., a mixture of calcium silicate gel and PEG-400 powder) was added to the basic formulation of O 42.5R cement mass concrete at a total mass of 1.5 wt% of cementitious material as experimental group 8-3.
[0163] Following the same testing method as in Test Example 1, the peak hydration temperature rise, peak duration, and total heat release of cement over 7 days for test groups 8-1 to 8-3 were measured and compared with the peak hydration temperature rise, peak duration, and total heat release of cement over 7 days for the blank group and test group 1-1 in Test Example 1. The change rate of total heat release of cement over 7 days for test groups 8-1 to 8-3 relative to the blank group was calculated. The results are shown in Table 8.
[0164] Table 8. P values of blank control group and experimental groups 8-1 to 8-3, 1-1 Performance test results of O 42.5R cement mass concrete.
[0165]
[0166] Table 8 shows that, compared with the blank group, the experimental group 8-1 only reduced the peak hydration temperature rise by 8℃ and broadened the temperature peak by 3h, and reduced the total heat release by 10.67% over 7 days. This indicates that although the modified polycarboxylic acid ether ester alone can reduce the peak hydration temperature rise to a certain extent, it cannot effectively broaden the temperature peak, slow down the temperature peak, or guarantee the normal total heat release. Compared with the blank group, the peak hydration temperature rise, peak duration, and total heat release of cement over 7 days in experimental groups 8-2 and 8-3 remained basically unchanged. This indicates that polyethylene glycol / silica composite microspheres alone, calcium silicate gel alone, and PEG-400 mixed powder alone have no hydration regulation effect, and polyethylene glycol / silica composite microspheres alone have little effect on the total heat release over 7 days. Unlike experimental groups 8-1 to 8-3, experimental group 1-1 added the temperature-sensitive controlled-release microcapsules prepared in Example 1, which reduced the peak hydration temperature rise by 11°C, broadened the temperature peak by 23 hours, and reduced the total heat release by only 2.25% over 7 days.
[0167] As can be seen, the temperature-sensitive controlled-release microcapsules provided by this invention sequentially encapsulate modified polycarboxylate ether ester with a temperature-sensitive inner shell formed by polyethylene glycol / silica composite microspheres, a rigid outer shell formed by calcium silicate gel and PEG-400 mixed and cured. The double shell of "rigid outer shell + temperature-sensitive inner shell" effectively protects the modified polycarboxylate ether ester at temperatures below 40°C (e.g., room temperature). The phase expansion of the temperature-sensitive inner shell at 40 to 45°C enables precise release of the modified polycarboxylate ether ester. The modified polycarboxylate ether ester then selectively targets and regulates the accelerated hydration period of C3S. Through the synergistic cooperation of the double shell-core structure of "rigid outer shell + temperature-sensitive inner shell + C3S hydration-targeted regulation core material", the technical effect of "wide temperature peak reduction, basically unchanged total heat release, and no early stagnation" is achieved.
[0168] Comparative Example 6: Based on Example 1, only the amount of modified polycarboxylic acid ether ester was changed from 65 parts to 55 parts. The types of raw materials, the amounts of the remaining raw materials, and the preparation steps were exactly the same as in Example 1, and the control material was prepared.
[0169] Comparative Example 7: Based on Example 1, only the amount of modified polycarboxylic acid ether ester was changed from 65 parts to 75 parts. The types of raw materials, the amounts of the remaining raw materials, and the preparation steps were exactly the same as in Example 1, and the control material was prepared.
[0170] Comparative Example 8: Based on Example 1, only the amount of polyethylene glycol / silica composite microspheres was changed from 22 parts to 15 parts. The types of raw materials, the amounts of the remaining raw materials, and the preparation steps were exactly the same as in Example 1, and the control material was prepared.
[0171] Comparative Example 9; Based on Example 1, only the total amount of "calcium silicate gel and PEG-400" was changed from 13 parts to 7 parts, and the mass ratio of "calcium silicate gel and PEG-400" remained unchanged. The types of raw materials, the amount of other raw materials, and the preparation steps were exactly the same as in Example 1, and the control material was prepared.
[0172] Comparative Example 10: Based on Example 1, only the mass fraction of KH-550 ethanol solution was changed from 3wt% to 1wt%, while the types and amounts of other raw materials and the preparation steps were exactly the same as in Example 1, and the control material was prepared.
[0173] Test Example 9: P provided in test example 1 (1) The control material provided in Example 1, with a total mass of cementitious material of 1.2 wt%, was added to the basic formulation of O 42.5R cement mass concrete as test group 9-1; P provided in test example 1 (1) In the basic formula of O 42.5R cement mass concrete, 1.2wt% of the total mass of cementitious materials provided by comparative examples 6 to 8 were added respectively as experimental groups 9-2 to 9-4. P provided in test example 1 (1) In the basic formulation of O 42.5R cement mass concrete, 1.2wt% of the total mass of cementitious material provided in Example 1.1 was added as test group 9-5. P provided in test example 1 (1) In the basic formula of O 42.5R cement mass concrete, 1.2wt% of the total mass of cementitious materials provided by Comparative Example 9 was added to each of the following experimental groups: 9-6. P provided in test example 1 (1) In the basic formulation of O 42.5R cement mass concrete, 1.2 wt% of the modifier provided in Example 1.2 was added to each of the cementitious materials, as experimental groups 9-7. P provided in test example 1 (1) In the basic formula of O 42.5R cement mass concrete, 1.2wt% of the total mass of cementitious materials provided by Comparative Example 10 was added to each of the following experimental groups: 9-8. P provided in test example 1 (1) The basic formula of O 42.5R cement mass concrete was supplemented with the control material provided in Example 1.3, which was 1.2wt% of the total mass of cementitious material, as experimental group 9-9.
[0174] Following the same testing method as in Test Example 1, the peak hydration temperature rise, peak duration, total heat release of cement over 7 days, initial setting time, and 1-day compressive strength of test groups 9-1 to 9-9 were measured and compared with those of the blank group measured in Test Example 1. The change rate of total heat release of cement over 7 days for test groups 9-1 to 9-9 relative to the blank group was calculated. The results are shown in Table 9.
[0175] Table 9. P values of blank control group and experimental group 9-1 to 9-9 Performance test results of O 42.5R cement mass concrete.
[0176]
[0177] As shown in Table 9: Compared with the blank group, the experimental group 9-1 was doped with 1.2wt% of the temperature-sensitive controlled-release microcapsules prepared in Example 1, which reduced the hydration temperature rise by 10℃, extended the temperature peak duration by 22h, reduced the total heat release by less than 2% in 7 days, and showed excellent temperature peak reduction effect, while the total heat release remained basically unchanged; moreover, the initial setting time was only extended by 0.6h, and the 28-day compressive strength retention rate reached 98.4%, without affecting the setting of cement and the early strength development.
[0178] Experimental groups 9-2 and 9-3 were respectively doped with 1.2 wt% of the temperature-sensitive controlled-release microcapsules prepared in Comparative Example 6 (with modified polycarboxylate ether ester content below the lower limit) and the temperature-sensitive controlled-release microcapsules prepared in Comparative Example 7 (with modified polycarboxylate ether ester content above the upper limit). The results showed that when the modified polycarboxylate ether ester content was reduced to 55 parts, the peak temperature rise decreased by only 4℃ and the peak temperature broadened by only 6 hours, indicating a significantly weakened control effect. When the modified polycarboxylate ether ester content increased to 75 parts, although the peak temperature drop increased, the change rate of the total heat release over 7 days reached as high as 11%. The initial setting time was significantly extended to 19.8h, and the 1-day strength dropped sharply by 48%, indicating that the amount of modified polycarboxylate ether ester ≥60 parts is a necessary condition to ensure sufficient inhibition components and achieve effective temperature peak broadening. When the amount of modified polycarboxylate ether ester increased to 75 parts, although the temperature peak drop increased, the change rate of total heat release over 7 days became higher, the initial setting time was significantly extended, and the 1-day strength dropped sharply, indicating that the amount of modified polycarboxylate ether ester ≤70 parts is the critical upper limit to avoid excessive inhibition, maintain the total heat release basically unchanged, and achieve early strength.
[0179] Experimental groups 9-4 and 9-5 were respectively doped with 1.2 wt% of the temperature-sensitive controlled-release microcapsules prepared in Comparative Example 8 (with polyethylene glycol / silica composite microspheres at a lower limit) and the temperature-sensitive controlled-release microcapsules prepared in Example 1.1 (with a higher amount of polyethylene glycol / silica composite microspheres). The results showed that when the amount of polyethylene glycol / silica composite microspheres decreased to 15 parts, the peak temperature rise only decreased to 62℃, and the peak temperature broadened to 20 h, indicating insufficient temperature control. When the amount of polyethylene glycol / silica composite microspheres increased to 30 parts, the temperature peak control effect was basically the same as that of experimental group 9-1, but the material cost increased without bringing significant additional technical gains. This indicates that an amount of polyethylene glycol / silica composite microspheres ≥20 parts is a structural prerequisite for providing sufficient expansion driving force, ensuring uniform cracking of the wall material, and effective release of the inhibitor; an amount of polyethylene glycol / silica composite microspheres ≤25 parts can balance preparation cost while ensuring effectiveness.
[0180] Experimental groups 9-6 and 9-7 were respectively doped with 1.2 wt% of the temperature-sensitive controlled-release microcapsules prepared in Comparative Example 9 (the total amount of calcium silicate gel and PEG-400 was below the lower limit) and the temperature-sensitive controlled-release microcapsules prepared in Example 1.2 (the total amount of calcium silicate gel and PEG-400 was higher). The results showed that when the total amount of calcium silicate gel and PEG-400 was reduced to 7 parts, the temperature peak broadened only to 25 h, and the 1-day strength decreased slightly. This indicates that the rigid shell was too thin, resulting in insufficient room-temperature protection and premature release of some modified polycarboxylic acid ether esters, which weakened the targeted controlled-release precision and slightly interfered with early hydration. When the total amount of calcium silicate gel and PEG-400 was increased to 18 parts, the control effect was comparable to that of experimental group 9-1, but the thicker rigid shell increased the difficulty of cracking the temperature-sensitive controlled-release microcapsules at the target temperature, the temperature peak reduction did not increase significantly further, the rate of change of total heat release increased slightly, and the material preparation cost also increased. The results show that a total amount of ≥10 parts of calcium silicate gel and PEG-400 is necessary to ensure room temperature stability and precise controlled release; a total amount of ≤15 parts of calcium silicate gel and PEG-400 can achieve a reasonable balance between trigger sensitivity and material economy.
[0181] Experimental groups 9-8 and 9-9 were respectively doped with 1.2 wt% of the temperature-sensitive controlled-release microcapsules prepared in Comparative Example 10 (KH-550 concentration in the KH-550 ethanol solution was below the lower limit) and the temperature-sensitive controlled-release microcapsules prepared in Example 1.3 (KH-550 concentration in the KH-550 ethanol solution was higher). The results showed that when the KH-550 concentration in the KH-550 ethanol solution decreased to 1 wt%, the peak temperature rise only decreased by 3 °C and the peak temperature broadened only by 3 hours, indicating a minimal temperature regulation effect. Near failure was due to insufficient silane coupling agent, leading to inadequate amination of the polyethylene glycol / silica composite microspheres, weak chemical bonding with the modified polycarboxylic acid ether ester, and unstable primary core-shell structure. This resulted in premature leakage of the modified polycarboxylic acid ether ester during mixing or early hydration. When the KH-550 concentration in the ethanol solution increased to 7 wt%, the temperature peak control effect was not significantly different from that of experimental group 9-1, while the rate of change in total heat release slightly increased, and production costs were clearly increased. This demonstrates that a KH-550 concentration ≥2% is a key process parameter for ensuring the structural integrity of the temperature-sensitive controlled-release microcapsules and achieving temperature-sensitive targeted controlled release; a KH-550 concentration ≤5% can balance the modification effect with production costs.
[0182] While the present invention has been described with reference to specific embodiments, those skilled in the art will understand that various changes can be made without departing from the true spirit and scope of the invention. Furthermore, numerous modifications can be made to the subject, spirit, and scope of the invention to suit specific situations, materials, material compositions, and methods. All such modifications are included within the scope of the claims of the present invention.
Claims
1. A thermosensitive controlled-release microcapsule having a double-shell core structure, comprising, from the outside in, a rigid outer shell, a thermosensitive inner shell, and a C3S hydration-targeting regulation core material encapsulated by the thermosensitive inner shell.
2. The temperature-sensitive controlled-release microcapsule according to claim 1, characterized in that, By weight, the content of the C3S hydration-targeted regulation core material in the thermosensitive controlled-release microcapsule is 60-70 parts by weight, the content of the thermosensitive inner shell is 20-30 parts by weight, and the content of the rigid outer shell is 10-18 parts by weight.
3. The temperature-sensitive controlled-release microcapsule according to claim 1 or 2, characterized in that, The rigid outer shell is made of a mixture of calcium silicate gel and polyethylene glycol; and / or The inner shell of the temperature-sensitive body is made of polyethylene glycol / silica composite microspheres; and / or The C3S hydration-targeted regulation core material is a modified polycarboxylic acid ether ester.
4. The temperature-sensitive controlled-release microcapsule according to claim 3, characterized in that, In the rigid shell, the mass ratio of the calcium silicate gel to the polyethylene glycol is 2:1; Preferably, the polyethylene glycol is polyethylene glycol 400.
5. The temperature-sensitive controlled-release microcapsule according to claim 3, characterized in that, The phase transition temperature of the polyethylene glycol / silica composite microspheres is 40℃-45℃; and / or the phase transition volume is 15%-20%. Preferably, the particle size of the polyethylene glycol / silica composite microspheres is 50μm-80μm.
6. The temperature-sensitive controlled-release microcapsule according to claim 3, characterized in that, The polyethylene glycol / silica composite microspheres are surface modified with a silane coupling agent; Preferably, the silane coupling agent is γ-aminopropyltriethoxysilane.
7. The temperature-sensitive controlled-release microcapsule according to claim 3, characterized in that, The modified polycarboxylic acid ether ester is obtained by grafting maleic anhydride onto a polycarboxylic acid water-reducing agent. Preferably, the number-average molecular weight of the modified polycarboxylic acid ether ester is between 8,000 and 12,000.
8. The thermosensitive controlled-release microcapsule according to any one of claims 1 to 7, characterized in that, The temperature-sensitive controlled-release microcapsules have a particle size of ≤75μm.
9. A method for preparing thermosensitive controlled-release microcapsules as described in any one of claims 1 to 8, comprising the following steps: After preparing the C3S hydration-targeted regulation core material into a first emulsion, the temperature-sensitive body inner shell is wrapped around the surface of the emulsion droplet to obtain a single-shell capsule. The rigid outer shell is further wrapped around the surface of the single-shell capsule to produce the temperature-sensitive controlled-release microcapsule.
10. The method according to claim 9, characterized in that, The method includes: The modified polycarboxylic acid ether ester, emulsifier, and water are mixed and emulsified to obtain the first emulsion; Mix the polyethylene glycol / silica composite microspheres and the first emulsion, adjust the pH, and stir to coat the polyethylene glycol / silica composite microspheres onto the surface of the emulsion droplets to form the thermosensitive inner shell, thereby obtaining a second emulsion containing the single-shell capsule; The calcium silicate gel and polyethylene glycol are prepared into a sol, which is then dropped into the stirred second emulsion to react, causing the sol to deposit on the surface of the single-shell capsule, thus obtaining a first suspension containing a double-shell capsule. Anhydrous ethanol and the first suspension are mixed to crosslink and solidify the sol on the surface of the double-shell capsule to form the rigid outer shell, resulting in a second suspension containing the temperature-sensitive controlled-release microcapsules.
11. The method according to claim 10, characterized in that, Adjust the pH to 7.5 to 8.5; and / or The reaction was carried out at a temperature of 30±2℃ for a duration of 2.5 h; and / or The cross-linking and curing process was achieved by stirring at room temperature for 10 minutes.
12. The method according to claim 10, characterized in that, The polyethylene glycol / silica composite microspheres are first modified with a silane coupling agent, and then mixed with the first emulsion; and / or After cross-linking and curing, the rigid shell is further subjected to static aging to make it dense; and / or The second suspension was separated into solid and liquid phases, and the solid phase was collected, dried, and post-processed to obtain the temperature-sensitive controlled-release microcapsules.
13. The application of the thermosensitive controlled-release microcapsules according to any one of claims 1 to 8 or the thermosensitive controlled-release microcapsules prepared by the method according to any one of claims 9 to 12 in the control of temperature rise during concrete hydration.
14. The application according to claim 13, characterized in that, The dosage of the temperature-sensitive controlled-release microcapsules is 0.8 wt% to 2.0 wt% of the mass of the cementitious materials in the concrete.